Transforming demons : the true story of how a Seeker resolves his karma : from ancient Atlantis to the present-day /: the true story of how a Seeker resolves his karma : from ancient Atlantis to the present-day. (2021) - Thoresen, Are Simeon, 1952-
No abstract available